KUALITAS BURGER KALKUN AKIBAT SUBSTITUSI TEPUNG BERAS MERAH TERHADAP KADAR PROTEIN, KADAR SERAT, DAN KUALITAS ORGANOLEPTIK - Agustinus Toling; Erik Priyo Santoso; Akhadiah Afrilia; Sumarno Sumarno (BUANA SAINS, 2022)
This research aimed to determine the effect of brown rice flour on crude protein, crude fiber, and organoleptic quality in turkey burgers. This study used a Completely Randomized Design (CRD) method with four trials and four replications. There were 16 experimental samples included: P1 (0% brown rice flour: 15% tapioca flour), P2 (5% brown rice flour: 10% tapioca flour), P3 (10% brown rice flour: 5% tapioca flour), and P4 (15% rice flour raw : 0% tapioca flour). Parameters observed included protein content, crude fiber content, and organoleptic tests consisting of color, taste, aroma, and texture. The result showed that the higher the level of substitution of tapioca with brown rice flour, the redder the color of the turkey meat burger, and the higher the panelist's preference for the color of the turkey meat burger. However, as the level of substitution of brown rice flour with wheat flour increased, the panelists' preference for the taste of turkey burgers decreased. The best treatment based on organoleptic tests was found in burgers with a substitution level of 10% brown rice flour: and 5% tapioca flour, with an average protein content of 19.34% and crude fiber content of 13.50%.